Cryogenic Thermo-Optical Coefficient of SU-8 Measured Using a Racetrack Resonator at 850 nm - Salvador A. Medina-Rangel; Nicola Maraviglia; John O’Hara; Artem S. Vorobev; Simone Iadanza; Emanuele Pelucchi; Liam O’Faolain (Photonics)
SU-8 is an emerging polymer material for integrated optical circuits that has demonstrated good structural properties in a cryogenic environment. In this article, we investigate the thermo-optical properties of SU-8 for a wavelength <semantics>λ=850<mtext> </mtext>nm</semantics>, from room temperature to cryogenic temperature down to 14 K. To measure the material properties, we designed and fabricated SU-8 racetrack resonators via electron beam lithography. While cooling the device in a closed-cycle cryostat, we measured the resonance spectrum as a function of the temperature from which we determined the temperature-induced variations of the group and effective indices of the waveguide. With the aid of waveguide eigenmode simulations, we used these data to derive the temperature dependence of the SU-8 refractive index <semantics>nSU−8<mfenced separators="|">T</mfenced></semantics>. At room temperature (T~295 K), the thermo-optic coefficient <semantics>dnSU−8/dT=−5.3±0.2×10−5<mtext> </mtext>K−1</semantics>. At low temperature (T~14 K), <semantics>dnSU−8/dT=−1.27±0.05×10−4<mtext> </mtext>K−1</semantics>. Our research shows the potential of SU-8 photonics in a cryogenic environment, suitable for the integration with quantum light sources emitting in the near infrared (NIR).